Ballistic saturation velocity of quasi-2D low-dimensional nanoscale field effect transistor (FET) - Ismail, Razali (Amer Inst Physics, 2009)
The saturation velocity is found to be ballistic regardless of the device dimensions. The ballistic intrinsic velocity is based on streamlining of the randomly oriented velocity vectors in zero electric field. In the degenerate realm, the saturation velocity is shown to be the Fermi velocity that is independent of temperature but strongly dependent on carrier concentration. In the non-degenerate realm, it's becomes thermal velocity that depends only on the ambient temperature. The drain carrier velocity is revealed to be smaller than the saturation velocity due to finite electric field at the drain-end. An excellent agreement is revealed when comparing the model to 80nm fabricated MOSFET.